REPRESENTASI NEPOTISME DALAM WACANA VISUAL: KAJIAN MULTIMODAL SAMPUL TEMPO PASCAPILPRES 2024 - Abang Muhammad Dalil Maulana; Merry Andriani (SeBaSa)
This research examines the representation of Gibran Rakabuming Raka and Kaesang Pangarep on the cover of Tempo newspaper within the context of political nepotism allegations in Indonesia. Using a qualitative approach, the study applies multimodal analysis to uncover the visual meanings and narratives in the newspaper cover’s illustration and texts. Data were collected from several editions of Tempo’s newspaper featuring both sons of President Joko Widodo in various political nomination contexts. The analysis reveals that the illustrations on the newspaper covers depict Gibran and Kaesang as central figures benefitting from their positions as the president's children, often accompanied by elements of satire and criticism regarding nepotistic practices. Through the combination of visual elements and text, Tempo constructs a narrative that questions their political legitimacy amid the dynamics of national political contests. This research aims to provide insights into how mass media play a role in framing issues of nepotism and influencing public perceptions of political integrity during Jokowi's era.